LINEAR AVERAGING SCHEMES ON WEIGHTED GRAPHS - RODIAH (NIM : 10108067); Pembimbing : Dr. Yudi Soeharyadi, ISTI
This study aims to find iterative averaging weight schemes of a graph and its rate of convergent. Averaging is done linearly with iterative method. Linear averaging is related with the discrete Laplace operator that defined on a graph. Finite difference scheme for discretization of Laplace equation is one special case of this averaging. The effective averaging criteria given by the eigenvalues properties of the transition matrix. Numerical simulations are given for some examples. These simulations support the conjecture that the rate of convergence depends on the connection graph with rate of convergent is exponential.